1985
DOI: 10.1111/j.1528-1157.1985.tb05678.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced ACTH Content in Cerebrospinal Fluid of Children Affected by Cryptogenic Infantile Spasms with Hypsarrhythmia

Abstract: In view of the therapeutic efficacy of adrenocorticotropic hormone (ACTH) in the treatment of infantile spasms (IS) with hypsarrhythmia, we studied the cerebrospinal fluid (CSF) levels of ACTH in 15 children (4-10 months) affected by IS with hypsarrhythmia (eight cryptogenic forms, seven secondary to perinatal distress) and in age-matched controls. Lumbar puncture was performed in all but one case before any kind of treatment. In another case, CSF was collected 3 weeks after a spontaneous remission. Both ACTH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 18 publications
3
29
0
Order By: Relevance
“…Similar results were reported by Nalin et al, 28 who did not study cortisol and CRH and found no difference in beta-endorphin levels between patients and controls. No correlation with age or diurnal variability was investigated.…”
Section: Discussionsupporting
confidence: 80%
“…Similar results were reported by Nalin et al, 28 who did not study cortisol and CRH and found no difference in beta-endorphin levels between patients and controls. No correlation with age or diurnal variability was investigated.…”
Section: Discussionsupporting
confidence: 80%
“…High brain CRH levels are expected to reduce cerebrospinal fluid (CSF) levels of ACTH and of steroids [because chronic activation of CRH receptors leads to their desensitization (Hauger et al, 1993) and decreased ACTH release]. Indeed, several groups have independently reported reduced ACTH levels in IS patients compared with agematched controls (Nalin et al, 1985;Baram et al, 1992b;Heiskala, 1997). Thus, these data are consistent with enhanced levels of endogenous CRH in brains of youngsters with IS.…”
Section: B the Many Etiologies Of Is Activate The Corticotropin-relesupporting
confidence: 76%
“…Attempts have been made to measure CSF levels of CRH as well as of ACTH and cortisol, the major human GC. Nalin and colleagues [65] found a reduction in CSF ACTH levels in 15 infants with MIS. We have recently confirmed this finding in 14 patients controlled for age, stress levels, and diurnal hormonal variation [66].…”
Section: Human Evidence For the Crh-excess Theory Of Massive Infantilmentioning
confidence: 99%